Trends in sperm quality by computer-assisted sperm analysis of 49,189 men during 2015–2021 in a fertility center from China - Li, Yanquan; Lu, Tingting; Wu, Zhengmu; Wang, Zhengquan; Yu, Ting; Wang, Hanshu; Tang, Chunhua; Zhou, Yuchuan (Frontiers in Endocrinology, 2023)
Background: Sperm quality, including semen volume, sperm count, concentration, and total and progressive motility (collectively, “semen parameters”), has declined in recent decades. Computer-assisted sperm analysis (CASA) provides sperm kinematic parameters, the temporal trends of which remain unclear. Our objective was to examine the temporal trend of both semen parameters and kinematic parameters in Shanghai, China in recent years. Methods: This retrospective study analyzed semen parameters and kinematic parameters of 49 819 males attending our reproductive center by using CASA during 2015–2021. The total sample was divided into two groups: samples that surpassed the WHO guideline (2010) low reference limits (‘above reference limit’ group, ARL; n = 24575), and samples that did not (‘below reference limit’ group, BRL; n = 24614). One-way analysis of variance (ANOVA), Kruskal-Wallis test, independent samples t-test, and covariance analysis were used to assess the differences among groups. Year, age, and abstinence time were included in the multiple linear regression model of the ARL group to adjust confounders and depict trends in sperm quality. Results: Among all total sample, ARL and BRL groups, the age of subjects increased in recent years. Semen volume and sperm count showed declined tendency with years in total sample, ARL and BRL groups, and subgroup of age or abstinence time. While sperm velocities showed increased tendency with years on the contrary. The multiple linear regression model of ARL group, adjusting for age and abstinence time, confirmed these trends. Semen volume (β1= -0.162, CI: -0.172, -0.152), sperm count (β1= -9.97, CI: -10.813, -9.128), sperm concentration (β1=-0.535, CI: -0.772, -0.299), motility (β1=-1.751, CI: -1.830, -1.672), and progressive motility (β1=-1.12, CI: -0.201, -0.145) decreased with year. Whereas VCL (β1= 3.058, CI: 2.912, 3.203), VSL (β1= 2.075, CI: 1.990, 2.161), and VAP (β1= 2.305, CI: 2.224, 2.386) increased over time (all p < 0.001). In addition, VCL, VSL, and VAP significantly declined with age and abstinence time. Conclusions: Semen parameters declined while kinematic parameters increased over recent years. We propose that even though sperm count and motility declined over time, sperm motion velocity increased, suggesting a possible compensatory mechanism of male fertility.